Analisis Perbandingan Rencana Anggaran Biaya Perhitungan Kontraktor dengan Metode Perhitungan AHSP 2025 pada Proyek Pembangunan BRI Unit Setu Bekasi - Aditya Maulana; Era Agita Kabdiyono (Jurnal Teknik dan Science, 2025)
Indonesia is a developing country, and as such, many projects are underway or about to commence. In practice, there are often discrepancies between the budget prepared by the contractor and that prepared based on the AHSP 2025. This study aims to analyze the comparative Budget Plan (RAB) using two different approaches, namely the contractor's calculation method and the 2025 Work Unit Price Analysis (AHSP) method on the BRI Unit Setu Bekasi construction project. This study uses a descriptive-comparative quantitative approach, where all components of the structural work are analyzed in terms of unit prices of materials, labor wages, and tools based on both methods. The results show that the total budget cost based on the contractor's method is Rp. 1,995,455,880.00, while based on the 2025 AHSP method is Rp. 2,414,858,280.00. From these results, there is a difference of Rp. 419,402,400.00 or approximately 21%, where the contractor's method is lower in terms of total costs. This difference is caused by the flexibility of the contractor's method, which adjusts the unit price to field conditions and cost efficiency strategies, while the AHSP method is standard and administrative in nature according to the provisions of the Ministry of PUPR. This study contributes to choosing the most effective and efficient budget approach in construction projects. For the project implementers and owners, this comparison serves as an evaluative basis for preparing a realistic yet accountable budget.